Functionally dissimilar neighbours increase tree water use efficiency through enhancement of leaf phosphorus concentration. (17th June 2022) - Huang, Zhiqun; Ran, Songsong; Fu, Yanrong; Wan, Xiaohua; Song, Xin; Chen, Yuxin; Yu, Zaipeng
Abstract: Water use efficiency (WUE) is central to the global cycles of water and carbon. However, whether increasing tree diversity in forests can increase WUE remains poorly understood because the variation in WUE may result from multiple mechanisms acting concurrently. Disentangling their relative importance represents a major challenge. Here, we conducted a forest biodiversity experiment in subtropical China to assess the effects of neighbouring tree diversity on the foliar WUE of Cunninghamia lanceolata, a widespread tree plantation species in China. We measured foliar δ 13 C as a proxy for the change in intrinsic WUE. To disentangle the relative importance of water and nutrient‐mediated mechanisms in altering WUE, we determined foliar nutrient concentrations and foliar δ 18 O. Foliar δ 18 O was used as a surrogate for stomatal conductance and is known to be related to plant water use. Foliar WUE of focal trees increased with specific root length and leaf nitrogen content dissimilarities between focal trees and neighbours. The positive neighbourhood dissimilarity effect on foliar WUE was stronger under a more shaded neighbourhood. Foliar P concentration increased with neighbourhood specific root length dissimilarity. However, neither neighbourhood trait dissimilarities nor species richness significantly affect foliar δ 18 O. Results from structural equation model suggested that neighbourhood dissimilarity in specific root length indirectly enhanced foliar WUE and tree growth of focal trees via increasing foliar P concentration. Synthesis . Our results demonstrate the potential role of neighbourhood trait dissimilarity in modulating tree WUE in species‐rich communities. Our finding implies that the functional diversity of tree species at the local neighbourhood level has a fundamental ability to control water and nutrient cycles in forests. Abstract : Impacts of neighbourhood height index, functional dissimilarity and their interactions on foliar nutrient concentrations, intrinsic water use efficiency, and growth of Cunninghamia lanceolata . Solid blue and red arrows represent positive and negative effects, respectively. More functionally dissimilar neighbours directly improved the foliar water use efficiency, and indirectly through increasing foliar P concentration and mitigating negative effects of competition for lights. 摘要: 植物的水分利用效率深刻影响着全球生态系统的碳和水循环，然而科学家们对于树种多样性如何改变森林的水分利用效率还了解很少。主要原因是树木水分利用效率的变化是由多个机制(比如光合作用，气孔导度等)同时控制的，因此揭示这些机制在树种多样性与水分利用的关系中的相对作用非常重要。2019年3月我们在中国的南亚热带地区建立了一个树种多样性野外实验，来评估邻体树种多样性改变以后对目标树种杉木叶片水分利用效率的影响机制。杉木是中国最为重要，且最广泛种植的用材树种。2021年5月我们确定了目标树，采集了杉木叶片，评估了目标树周围一圈8棵邻体树木的性状和生长情况。我们分析了叶片的δ 13 C丰度，并用来指示叶片内在水分利用效率的变化。为了揭示水分和养分的改变在调控杉木叶片水分利用效率变化中的相对作用，我们还测定了杉木叶片的养分氮和磷浓度、以及叶片δ 18 O丰度。叶片δ 18 O丰度与植物水分可利用性有关，常常被用来指示叶片气孔导度的变化。我们的结果发现，目标树与邻体树木功能性状的差异(比如，树木比根长差异和叶氮含量的差异)越大，目标树叶片的内在水分利用效率越高。如果邻体树越高，对目标树构成的遮阴效果越大，那么这种功能性状差异造成的水分利用效率提升效果会越明显。目标树与邻体树功能性状的差异也显著增加了目标树叶片的磷含量，但对叶片δ 18 O丰度没有影响。结构方程模型分析表明，目标树与邻体树功能性状的差异间接通过增加目标树的叶磷含量来增加叶片的水分利用效率。因此，在亚热带地区，邻体树种多样性增加很可能是通过改善目标树的养分水平、增加植物光合能力，从而提高树木水分利用效率的。我们的结果揭示树木功能性状差异的增加、而不是树种丰富度的增加在改变树木水分利用效率中的角色，强调了邻体水平多样性与目标树互作研究在揭示和理解群落水平多样性与生态系统功能关系中扮演关键角色。.